PENDAMPINGAN DAN PEMBINAAN PERILAKU HIDUP BERSIH DAN SEHAT IBU DAN ANAK PEMULUNG DI PASIR PANJANG KOTA KUPANG - Sheldena, Devi; Philia Octavianus; Delsi Humau; Dewi Banfatin; Arwadi Rehe Poti; Kevin Manu (Education and Talent Development Center of Indonesia, 2024)
Health and hygiene issues often arise in society, especially among scavengers. The government has long implemented the Clean and Healthy Living Behavior Program (PHBS) in the work environment, namely the Final Waste Disposal Site (TPA), but it is often not paid attention to. The aim of community service activities for the Christian Psychology Study Program is to increase the understanding and skills of scavengers regarding clean and healthy living behavior in the environment. The method of community service activities carried out in the AquAda scavenger group environment is health and hygiene education to mothers and children of scavengers regarding Clean and Healthy Health Behavior (PHBS) in the work environment with lectures, discussions and practice. The evaluation method used is the reaction and learning method. The service was carried out in Pasir Panjang Village on 27 and 28 July 2023 involving mothers and children who were scavengers. The evaluation result of this service activity was an increase in the knowledge of scavenger mothers and children about the importance of health and cleanliness in the environment. Apart from increasing the knowledge and skills of mother and child scavengers, this service activity is able to raise awareness of mother and child scavengers to maintain personal and environmental cleanliness to remain safe and comfortable. The scavengers were very satisfied with trainer 1 (67%) and trainer 2 (73%) based on the delivery of the material. Meanwhile, the majority of participants felt very satisfied with trainer 1 (53%) and trainer 2 (60%) based on mastery of the material. Mother participants experienced an increase in changes from the pretest score to the posttest score. However, there were participants whose results were not optimal. It can be concluded that this assistance must be carried out regularly. Because a person's behavior cannot be permanent if it is only done once. Meanwhile, children showed a change in the scores of participants before and after being given assistance. At the pretest, 53% of the participants were in the medium category and 47% of the participants were in the high category. After being given training, the results of the posttest were 7% of participants in the high category and 93% in the very high category.